Organic tandem solar cells under indoor light illumination. (9th June 2020) - Biswas, Swarup; You, Young‐Jun; Vincent, Premkumar; Bae, Jin‐Hyuk; Shim, Jae Won; Kim, Hyeok
Abstract: The lifetime of a device depends highly on that of its battery. In order to enhance the longevity of microsystems or sensor networks, it is necessary for these devices to be self‐powered. Indoor photovoltaics allow the possibility of harvesting artificial light sources for powering microsystems. Whereas indoor photovoltaics based on single active layers have showed high efficiencies under LED lighting, tandem structures have yet to be tested extensively. In our study, we use finite‐difference time‐domain simulations to study the highest possible short‐circuit current density that can be extracted from tandem organic devices. We compare the simulation results to the results for photovoltaic devices based on single bulk active layer heterojunctions. Our simulations found that although detailed balanced band gap calculations show tandem photovoltaics to be viable, the low‐intensity emission spectra of white LED light sources can be better harvested by single active layer‐based photovoltaics. The current‐matching limitation of a tandem photovoltaic structure connected in series limits the highest output current and open‐circuit voltage of the device and, thus, its performance for the illumination of lower intensity light. Abstract : Organic tandem solar cell with the active materials having optimized band gap and thickness is tested under low‐intensity indoor light. The current‐matching limitation of a tandem photovoltaic structure connected in series limits the highest output current and open‐circuit voltage at low‐intensity light. Therefore, the tandem solar cell constructed with active materials having optimized band gaps and thicknesses is less efficient than single‐celled photovoltaic device for indoor application.